Subcellular origin of mitochondrial DNA deletions in human skeletal muscle. Issue 2 (21st August 2018) - Vincent, Amy E.; Rosa, Hannah S.; Pabis, Kamil; Lawless, Conor; Chen, Chun; Grünewald, Anne; Rygiel, Karolina A.; Rocha, Mariana C.; Reeve, Amy K.; Falkous, Gavin; Perissi, Valentina; White, Kathryn; et al.
Abstract : Objective: In patients with mitochondrial DNA (mtDNA) maintenance disorders and with aging, mtDNA deletions sporadically form and clonally expand within individual muscle fibers, causing respiratory chain deficiency. This study aimed to identify the sub‐cellular origin and potential mechanisms underlying this process. Methods: Serial skeletal muscle cryosections from patients with multiple mtDNA deletions were subjected to subcellular immunofluorescent, histochemical, and genetic analysis. Results: We report respiratory chain–deficient perinuclear foci containing mtDNA deletions, which show local elevations of both mitochondrial mass and mtDNA copy number. These subcellular foci of respiratory chain deficiency are associated with a local increase in mitochondrial biogenesis and unfolded protein response signaling pathways. We also find that the commonly reported segmental pattern of mitochondrial deficiency is consistent with the three‐dimensional organization of the human skeletal muscle mitochondrial network. Interpretation: We propose that mtDNA deletions first exceed the biochemical threshold causing biochemical deficiency in focal regions adjacent to the myonuclei, and induce mitochondrial biogenesis before spreading across the muscle fiber. These subcellular resolution data provide new insights into the possible origin of mitochondrial respiratory chain deficiency in mitochondrial myopathy. Ann Neurol 2018;84:289–301